Probing the Damage Recovery Mechanism in Irradiated Stainless Steels Using In-Situ Microcantilever Bending Test - Mao, Keyou S.; Wang, Hao; Qu, Haozheng J.; Yano, Kayla H.; Edmondson, Philip D.; Sun, Cheng; Wharry, Janelle P. (Frontiers in Materials, 2022)
Single crystalline microcantilevers are fabricated from the base metal and heat-affected zone (HAZ) of a laser welded, neutron irradiated austenitic stainless steel, for scanning electron microscope (SEM) in-situ bending. In the HAZ, cantilevers exhibit higher yield point and lower crack tip blunting displacement than in the base metal and unirradiated archive specimen. These results suggest that radiation-induced defects harden the base metal, whereas the HAZ exhibits annealing of defects leading to mechanical softening. Dislocation nucleation ahead of the crack tip is responsible for ductile blunting behavior and provides a pathway to mitigating helium-induced cracking during weld repairs of irradiated materials.